2018
DOI: 10.17140/otloj-4-146
|View full text |Cite
|
Sign up to set email alerts
|

Surgıcal Techniques for the Treatment of Concha Bullosa: A Systematic Review

Abstract: As there is no defined technique for surgery of concha bullosa the aim of this article is to review the literature and compare different techniques used for concha bullosa reduction. Methods A structured review of the PubMed, Embase and Cochrane Collaboration databases (Cochran Central Register of Controlled Trials, Cochran Database of Systemic Reviews) was undertaken, using the terms: conchabullosa, turbinoplasty, partial middle turbinectomy and pneumatized middle turbinate. Results Total of 142 articles were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The prevalence of left CB (24.6%) was more frequent as compared to the right one (18.9%) with statistically significant difference (P=0.033). On the contrary, in an Indian study reported by Kalaiarasi et al [17], out of the 202 CB can imping on the infundibulum and ostium of maxillary, anterior ethmoid, and frontal sinuses causing a negative effect on their ventilation making them more prone to infection [23,10]. Also, there is a strong relationship between the incidence of CB and contralateral nasal septal deviation [1].…”
Section: B B a Amentioning
confidence: 96%
See 1 more Smart Citation
“…The prevalence of left CB (24.6%) was more frequent as compared to the right one (18.9%) with statistically significant difference (P=0.033). On the contrary, in an Indian study reported by Kalaiarasi et al [17], out of the 202 CB can imping on the infundibulum and ostium of maxillary, anterior ethmoid, and frontal sinuses causing a negative effect on their ventilation making them more prone to infection [23,10]. Also, there is a strong relationship between the incidence of CB and contralateral nasal septal deviation [1].…”
Section: B B a Amentioning
confidence: 96%
“…Nevertheless, nowadays many different surgical approaches for CB treatment are used, such as endoscopic lateral or medial partial resection, turbinoplasty, total resection, crushing and crushing with intrinsic stripping. However, there is no obvious consensus about which is the best surgical option yet [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Resection of middle turbinate has been described but is not generally recommended. 20 In our practice we used the excision of lateral lamella and crushing techniques and found both methods equally effective in relieving patient symptoms.…”
Section: Comparisons With Other Studiesmentioning
confidence: 97%
“…Different techniques have been described for concha bullosa surgery including crushing, partial turbinectomy (medial or lateral) and complete middle turbinectomy. 20 The lateral partial resection of turbinate involves removing only the lateral lamella of the concha, it is widely used but the possibility of synechia formation is a disadvantage with this technique. Crushing of the concha bullosa is a fairly effective technique and can be done if the concha is not extensive.…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
“…Concha bullosa is an anatomical variation of the lateral nasal wall, characterised by the presence of an air pocket within the middle turbinate. 1 A large concha bullosa can narrow the middle meatus, and reduce the mucociliary clearance and ventilation, causing obstruction of the osteomeatal complex. Concha bullosa becomes pneumatised as a result of ethmoid cell extensions.…”
Section: Introductionmentioning
confidence: 99%